Qichwa Yaru (Pasco-Huánuco): Issues, revisions, and continuity - Domínguez Condezo, Víctor (2021)
The present work constitutes a current analysis of the problematic situation in our millenary language: Qichwa, on the 200th anniversary of the Peruvian Republic. In this context of identity revaluation, the objective is to contribute to the assertion of our first national language. The methodology applied was observational and descriptive-analytical. We consulted studies from the time of the Spanish invasion, such as the book Arte y Vocabulario en la Lengua General del Perv, llamada Quichua, y en la lengua Española by Fray Domingo de S. Thomas (1560), as well as several recent linguistic and pedagogical studies. As a preliminary result, we argue that in these regions, the Qichwa language has suffered interference from Spanish culture through distortions and discriminations to the Andean society during the colonial and republican periods. We conclude that our Qichwa language is devalued, distorted, and greatly affected in its syntactic structure, morphology, phonetics, with notoriety in its senses and meanings.